Analisis Isi Pesan Komunikasi pada Kampanye "Don't Know? Kasih No!" di YouTube Solusi BCA dalam Upaya Edukasi Pencegahan Cybercrime - Rafli Argireza Akbar; Dian Hutami Rahmawati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The rise of cybercrime in Indonesia’s digital financial services demands effective and communicative public education. This study aims to explore how educational communication messages for cybercrime prevention are represented in BCA’s “Don’t Know? Kasih No!” campaign published on YouTube. Using a qualitative content analysis approach, the study focuses on interpreting both verbal and visual message meanings based on Rice and Atkin’s Public Communication Campaign theory. Findings reveal that the campaign constructs digital security education through several key strategies: simplifying technical concepts, providing practical behavioral instructions, reinforcing vigilance through communicative visual elements, engaging the public in participatory message dissemination, and utilizing humor and nostalgia as cultural anchoring. This multidimensional approach successfully delivers messages that are not only informative but also persuasive and easily accepted across diverse societal groups.